A Scientometric Review of Global Research on Information Literacy and Visually Impaired - Varma, Akhilesh Kumar; Singh, Kunwar; Gireesh Kumar, T. K. (Journal of Information and Knowledge, 2020)
The term information literacy has different meanings, but it is a skill that every individual must possess to effectively achieve their personal, social, educational, and work goals. This skill set helps to identify, evaluate, and effectively use information. Visually impaired people need to receive specialized services and tools to enhance their information literacy skills to enable them to work independently and effectively. The main aim of the study is to examine the growth and development of published literature on information literacy that focuses primarily on visually impaired people. Between 1990 and 2018, the global production of publications identified by the Scopus database provided the basis for this study. A search of the Scopus database showed that 589 scientific publications had appeared on the world stage. The paper presents an analysis of the data.